Morishitium polonicum (Machalska, 1980) is a junior synonym of Morishitium dollfusi (Timon-David, 1950) (Trematoda: Cyclocoeliidae) - Heneberg, Petr; Sitko, Jiljí (Parasitology research, 2023)
Species of the genus Morishitium Witenberg, 1928 are parasites of the body cavity, air sacs, and lungs of birds. At least 14 species are considered valid, but molecular confirmation of their status is lacking. Here, we provide the first molecular data on Morishitium dollfusi isolated from their type host Pica pica, compared them with previously reported molecular data from Morishitium polonicum isolated from their type and paratype hosts, Turdus merula and Turdus philomelos, and performed extensive measurements of 511 individuals of Morishitium spp. across a broad host spectrum, at multiple infection intensities, and year-round. We analyzed the molecular phylogenetics of Morishitium spp. adults isolated from bird hosts of Czech origin and provide comparative measurements of the analyzed specimens. Based on the molecular examination of morphologically identified specimens of M. dollfusi and M. polonicum (CO1, ND1, and ITS2 markers), we propose synonymization of Morishitium dollfusi (Timon-David, 1950) with Morishitium polonicum (Machalska, 1980) (isolates of European origin). The three markers were either identical (CO1, ITS2) or formed haplotypes shared by the two species (ND1). Morphological analyses revealed a continuum of key identification features for the two above-named species, although we used specimens matching the original descriptions and isolated them from the type hosts. Therefore, Morishitium polonicum is a junior synonym of Morishitium dollfusi. Attention is needed regarding the status of East Asian isolates identified previously as M. polonicum (or M. polonicum malayense). The molecular analysis revealed that these isolates form a distinct clade, and further research is needed to produce data allowing the likely separation of the malayense clade as a separate species.
Keywords: Animals; Trematoda; Digenea; Songbirds; Cyclocoeliidae; Pica; Helicella; zpěvní ptáci; Passeriformes; lidé; Aves; Phylogeny; Lungs; Lizards; ještěři; Xerothermic snails; zvířata; pika; fylogeneze; Humans